KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PADA MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Sari, Intia; Asmara, Adi (Universitas Muhammadiyah Bengkulu, 2016)
This study aimed to see differences in the ability of understanding the mathematical concepts that students taught through cooperative learning model jigsaw with conventional learning on eighth grade students of SMPN 18 Bengkulu academic year 2013/2014. This research is a quasi experimental study. The study population is the entire eighth grade students of SMP Negeri 18 Bengkulu city. The research sample determined by random sampling technique and obtainedÂ VIII.2 classes to taling 30 students as classroom control, and VIII.3 graders who totaled 30 students as a class experiment. The data collected is the data from the pre-test and post-test students' comprehension of Â mathematical concepts, the data were analyzed using t-test. The results of this study indicate that while t table t count=2.1652785=2.00172 which means that there are differences in the ability of students' understanding of concepts taught through cooperative learning model jigsaw with conventional learning on eighth grade students of SMPN 18 Bengkulu academic year 2013/2014. Based on the results of this study concluded that the Jigsaw cooperative learning model affect the ability of students 'understanding of the concept compared to conventional learning, so that there are differences inthe ability ofstudents'understanding of mathematical concepts of these two classes.Keywords: ability of understanding the mathematical concepts, Jigsaw cooperative learning model